Engineering Blood and Lymphatic Microvascular Networks in Fibrin Matrices - Knezevic, Lea; Schaupper, Mira; Mühleder, Severin; Schimek, Katharina; Hasenberg, Tobias; Marx, Uwe; Priglinger, Eleni; Redl, Heinz; Holnthoner, Wolfgang (Frontiers in Bioengineering and Biotechnology, 2017)
Vascular network engineering is essential for nutrient delivery to tissue-engineered constructs and, consequently, their survival. In addition, the functionality of tissues also depends on tissue drainage and immune cell accessibility, which are the main functions of the lymphatic system. Engineering both the blood and lymphatic microvasculature would advance the survival and functionality of tissue-engineered constructs. The aim of this study was to isolate pure populations of lymphatic endothelial cells (LEC) and blood vascular endothelial cells (BEC) from human dermal microvascular endothelial cells (HDMEC) and to study their network formation in our previously described co-culture model with adipose derived stromal cells (ASC) in fibrin scaffolds. We could follow the network development over a period of four weeks by fluorescently labelling the cells. We show that LEC and BEC form separate networks, which are morphologically distinguishable and sustainable over several weeks. In addition, lymphatic network development was dependent on vascular endothelial growth factor (VEGF)-C, resulting in denser networks with increasing VEGF-C concentration. Lastly, we confirm the necessity of cell-cell contact between endothelial cells and ASC for the formation of both blood and lymphatic microvascular networks. This model represents a valuable platform for in vitro drug testing and for the future in vivo studies on lymphatic and blood microvascularization.